2015
DOI: 10.1039/c4ta05606j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient titanium nitride/titanium oxide composite photoanodes for dye-sensitized solar cells and water splitting

Abstract: Efficient titanium nitride/titanium oxide (TiN/TiO 2 ) composite photoanodes have been proposed for the use not only in dye-sensitized solar cells (DSSCs) but also for water splitting. When the TiN precursor films were sintered at 500 C for 0.5 to 4 h, they were partially converted to crystalline TiO 2 containing both rutile and anatase phases. For the DSSCs, higher TiN content in the photoanodes resulted in a more negative flat-band potential and higher conductivity but lower surface area for the dye adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Now the Mott‐Schottky equation for semiconductor electrode is given by: true1Cs2=2ϵϵ0ea2Nd4pt[V-Vfb-kTe] …”
Section: Resultsmentioning
confidence: 99%
“…Now the Mott‐Schottky equation for semiconductor electrode is given by: true1Cs2=2ϵϵ0ea2Nd4pt[V-Vfb-kTe] …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Titanium Nitride (TiN) has sparked as a potential candidate for broadband absorption covering the entire visible-infrared regions of the electromagnetic spectrum with a surplus benefits such as low loss and cost, high thermal and oxidative stability, unlike Au and Ag. TiN is fully compatible with the existing CMOS fabrication techniques in addition TiN exhibits biocompatibility [19,31,32,33].…”
Section: Observed the Absorption Enhancement Using Silver Nanoparticlmentioning
confidence: 99%
“…The following Figure 9 shows the polarization curve of HER FeOOH@Co 4 N. Mohamed et al (2020) synthesized TiN/TiO x N y bilayer films using D.C reactive magnetron sputtering. Li et al (2015) reported that in a bilayer film a higher TiN layer causes a more negative flat -band value. In the case of water splitting, a more negative band value helps to provide a larger driving force to trigger water redox.…”
Section: Water Splittingmentioning
confidence: 99%